Morals in multi-unit markets - Andreas Ziegler; Giorgia Romagnoli; Theo Offerman (Tinbergen Institute, 2020)
Recent work examines whether morals are eroded in single-unit markets (Falk & Szech, 2013; Bartling, Fehr & Ozdemir, 2020). These markets provide market power to individual traders, which limits the roles of two forces; (i) replacement logic, whereby immoral trading is justified by the belief that others would trade otherwise; (ii) market selection, by which the least moral trader determines quantities. In an experiment, we compare single-unit to (more common) multi-unit markets which may activate these forces. We find that, in contrast to single-unit markets, multi-unit markets show full erosion of morals. Especially the replacement logic drives this finding.
Keywords: D62; C91; C92; 330; replacement logic; social responsibility; markets; externalities; competition; charity